P–553 Women with molar pregnancies have a genetic susceptibility to aneuploid miscarriages. (6th August 2021) - Slim, R; Khawajkie, Y; Hoffner, L; Tan, L; Ab. Rafea, B; Aguinagua, M; Horowitz, N S; Ao, A; Tan, S L; Brown, R; Buckett, W; Surti, U; et al.
Abstract: Study question: What causes non-molar miscarriages in women with one hydatidiform mole (HM)? Summary answer: We found a higher rate of aneuploidies in the non-molar miscarriages of women with HM than in those from women with sporadic or recurrent miscarriages. What is known already: Women with hydatidiform moles have higher rates of miscarriages and women with recurrent miscarriages have higher rates of moles than women from the general population. Study design, size, duration: We retrieved archived formalin-fixed paraffin embedded tissues from non-molar miscarriages of patients with one HM and analyzed them for the presence of aneuploidies using single nucleotide polymorphism (SNP)-microarray. We next determined the meiotic origin of the aneuploidies by genotyping the aneuploid non-molar miscarriages along with the parental genomes using microsatellite markers. Participants/materials, setting, methods: All participants and some of their partners provided written consent to participate in our study, agreed to a blood draw for genotyping analysis, and agreed for us to retrieve their molar and non-molar tissues from various histopathology laboratories for research purposes. Main results and the role of chance: We demonstrate for the first time that patients with an HM and miscarriages are at higher risk for aneuploid miscarriages [83.3%, 95% confidence interval (CI): 0.653–0.944] than women with sporadic (51.5%, 95% CI: 50.3–52.7%, p value = 0.0003828) or recurrent miscarriages (43.8%, 95% CI: 40.7–47.0%, p value = 0.00002). Genotyping the aneuploid miscarriages and the parental genomes demonstrated that most of the aneuploidies originated from errors in maternal meiosis I or II. Limitations, reasons for caution: We were able to retrieve only 30 non-molar miscarriages from women with one HM for analysis. Expanding such analysis to a larger and independent cohort of miscarriages from such patients will be important to validate our observations. Wider implications of the findings: Our data suggest common genetic female germline defects predisposing to HM and aneuploid non-molar miscarriages in some patients. Trial registration number: Not applicable